Utilization of Augmented Reality Technology in Independent Speech Therapy Applications - Wanti, Linda Perdana; Somantri, Oman; Kartiyani, Titin (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 15 No 1 (2024): Vol. 15, No. 1 April 2024DO - 10.24843/LKJITI.2024.v15.i01.p01, 2024)
One of the uses of information technology is augmented reality technology in the health sector. Augmented reality is used in the development of applications that are used for speech therapy for children with autism or children with speech delays. The method used for the development of speech therapy applications is the extreme programming method. This method can adapt to the development of an application in a short time and quite a lot of changes. The stages in the extreme programming method include identifying system requirements, planning activities during system/application development, system development process, iteration for system improvement until the final iteration, and no more user feedback, system/application production, and system maintenance with data backup and system recovery. After testing the system, it was concluded that three iterations occurred during the development of the speech therapy application. The last test showed that the user accepted the speech therapy application with a percentage of 77,14%. The output of this research is an augmented reality-based speech therapy application that is useful for independent speech therapy for children with speech delays.